Entropies and Fisher information matrix for extended beta distribution (2015)
ABSTRACT: The extended beta type 1 distribution has the probability density function proportional to x α−1 (1 − x) β−1 exp[−σ/x(1 − x)], 0 < x < 1. In this article, we derive the Fisher information matrix and entropies such as R´enyi and Shannon for the extended beta type 1 distribution.